In Memory of Leonid Leonidovich Kasatkin (30.12.1926–13.09.2020) - Morozova, Nadezhda (Slavistica Vilnensis, 2020)
Leonid Kasatkin is a famous Russian dialectologist. He devoted his works to Russian phonetics, the study of dialects, especially of the Old Believers. He often came to Vilnius University for conferences, for many years he had creative contacts with prof. Chekmonas. His contribution to science is very significant.
Keywords: Leonid Kasatkin; Russian dialectology; ad memoriam; Old Believers